FAKTOR-FAKTOR YANG MEMPENGARUHI APARATUR PEMERINTAH DAERAH DALAM MENERAPKAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL (Studi Empiris pada Kabupaten Tulang Bawang Barat Lampung) - Wahyu Pratiwi (AKT 15 UMY 299, 2015)
*299 The purpose of this research is analyze and know empirical evidence about the apparatus on local government in applying government accounting standards accrual in regency of Tulang Bawang Barat Lampung especially apparatus on local government who have experience of more than a year and test the various affecting factor of apparatus on local government start to attended training, educational background, quality of facilities, and information systems suspected of having implementation effect government accounting standards This research use primary data. Primary data derived from quistionare. The quistionare be delivered for apparatus on local government in regency of Tulang Bawang Barat involved in preparation report local finances. Total sample is 48 apparatus on local government. Analytical data in this research is multiple regression. The result of this research is attended training and educational background have significantly the level of understanding in applying government accounting standards accrual